2020
DOI: 10.1021/acsinfecdis.0c00068
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Amphamide, a Drug Candidate for the Second Generation of Polyene Antibiotics

Abstract: Amphotericin B (AmB, 1) is the drug of choice for treating the most serious systemic fungal or protozoan infections. Nevertheless, its application is limited by low solubility in aqueous media and serious side effects such as infusion-related reactions, hemolytic toxicity, and nephrotoxicity. Owing to these limitations, it is essential to search for the polyene derivatives with better chemotherapeutic properties. With the objective of obtaining AmB derivatives with lower self-aggregation and improved solubilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
1
30
0
2
Order By: Relevance
“…It was found that AmB at concentrations about an order of magnitude higher than MIC, self-associate to form dimers or higher oligomers, that are equally toxic to mammalian and fungal cells, whereas AmB monomers, dominating at concentrations close to MIC, are selectively fungicidal [ 9 ]. Several attempts have been made to improve selective toxicity of AmB by its chemical modifications, mainly at the amino group of mycosamine or the carboxyl functionality, resulting in disturbance of self-association ability [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that AmB at concentrations about an order of magnitude higher than MIC, self-associate to form dimers or higher oligomers, that are equally toxic to mammalian and fungal cells, whereas AmB monomers, dominating at concentrations close to MIC, are selectively fungicidal [ 9 ]. Several attempts have been made to improve selective toxicity of AmB by its chemical modifications, mainly at the amino group of mycosamine or the carboxyl functionality, resulting in disturbance of self-association ability [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most well-known polyene, amphotericin B (AmB), is one of the most potent fungicidal agents on the market with a broad-spectrum of activity, shown to be effective against Cryptococcus spp. and most Candida spp., but several next generation drugs have been in the making [ 3 , 4 , 5 ]. (ii) Azoles are a class of antifungal drugs that target lanosterol-14α-demethylase (Erg11), which catalyzes the demethylation of lanosterol to make an important precursor that is eventually converted into ergosterol [ 6 , 7 ].…”
Section: Fungal Infections In Humans and Current Antifungal Drugsmentioning
confidence: 99%
“…Выбор доз для исследования был основан на результатах, полученных при изучении острой токсичности препарата [11]. Лиофилизат растворяли в 5 % растворе глюкозы и в 1 % концентрации вводили внутрибрюшинно ежедневно в течение 30 дней с интервалом 24 ч в разовых дозах 0,07 (1 / 30 максимальнопереносимой дозы (МПД)) и 0,17 мг/кг (1/30 ЛД 50 ).…”
Section: материалы и методыunclassified
“…В ФГБНУ «НИИНА» разработаны методы химической трансформации полиеновых антибио тиков. Получены серии полусинтетических аналогов, изучена их биологическая активность [11]. Среди новых соединений, перспективных для дальнейшего изучения, было отобрано полусинтетическое производное N-(2-аминоэтил)амид амфотерици на В (амфамид), проявившее ряд преимуществ перед амфотерицином в экспериментах in vivo [11].…”
Section: Introductionunclassified